Primary School Earth and Space Science Educational Game Application - Ahmad Harnaini, Ain Fatihah (IRC, 2019)
As Vision 2020 approaches, Malaysians have yet to overcome the challenge of being a progressive society that does not just simply act as consumers of technology, but also be capable of contributing to the scientific and technological civilization of the future. Majority of students choose not to pursue into STEM related studies as they are slowly losing interest and the engagement to learn STEM education due to limited availability of interactive teaching method and tools for a more effective learning in the classroom environment. With respect to the matter, games have been introduced over the years as an exciting approach to retain students’ interest in learning using current software like mobile applications. Hence in this regard, an educational game application is proposed to assist in increasing student’s interest in STEM subjects, mainly focusing on the Earth and Space Science topic. The purpose of this project is to study how educational game application can help to incline students’ interest in Science subject, develop an educational game application and conduct usability evaluation of the educational game application. The research covers the scope to the targeted group of Year 4 and Year 5 primary school students and the subtopic chosen is Earth and space science. The project utilizes Rapid Application Development methodology due to the short amount of time. The application was developed using Ionic Framework, Angular 5, C#.NET and SQLExpress. The findings showed that this project is believed to be helpful to incline students’ interest in learning Science subject.